The Kazakh folklore corpus: scientific approaches and research perspectives - Aitova, Н.Н.; Bakytkyzy, М. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
In line with the main strategy of our country aimed at the digitalization of the humanities, in recent years, there has been a growing interest in creating textual databases. This trend is recognized as part of global developments of contemporary importance. This article explores the opportunities for scientific text analysis and research offered by the development of “The Kazakh Folklore Corpus.” The study aims to analyze the significance of systematizing samples of Kazakh oral literature through corpus linguistics methods in order to identify their linguistic, structural, and semantic features. The main areas of the study include the collection of texts, their digitization, morphological and semantic annotation, concordance creation, and statistical analysis of linguistic units. The scientific significance of the research lies in establishing the prerequisites for building a linguistic corpus database that enables the study of Kazakh folklore at a new level, analyzing its textual structures using modern methodologies, and introducing the rich layers of the language into academic circulation. The key results include the presentation of a corpus model of Kazakh folklore texts and the demonstration of its potential for comprehensive linguistic analysis. This study opens up a new research space in Kazakh linguistics by adapting the theory and practice of corpus linguistics to national folklore and contributes a methodological basis to the development of Kazakh folklore studies.